Frequent coconut milk intake increases the risk of vascular disease in adults - Sulistyowati Tuminah; Marice Sihombing (Faculty of Medicine, Universitas Trisakti, 2015)
Background Coconut milk is an essential ingredient of the Indonesian cuisine. In view of its saturated fatty acid content, coconut milk has frequently been blamed as a cause of cardiovascular disease. The objective of this study was to determine any association between coconut milk intake and vascular disease among adults.MethodsA cross-sectional study was conducted in 2011-2012 on adults aged 25-65 years. Self-reported health and nutritional data were collected by means of questionnaire-based interviews, with the aid of 3-D food models. Medical data comprised blood pressure and anthropometry (waist circumference and body mass index), neurological status, ECG, blood glucose and lipid profile. Data analysis was done using multiple logistic regression. ResultsA total of 4,187 respondents fullfilled the inclusion criteria. Frequent coconut milk intake (>3 times/week) significantly increased the risk of vascular disease by 1.3-fold compared with infrequent coconut milk intake (<2 times/week) (OR=1.33; 95% CI: 1.11-1.60; p=0.002) after controlling for age, gender, hypertension, diabetes mellitus and stress. The influence of coconut milk intake on vascular disease risk was lower than that of age, gender, hypertension and diabetes mellitus. ConclusionFrequent coconut milk intake increased the risk of vascular disease in adults. Further investigations are needed about the effect of coconut milk intake on noncommunicable diseases.